2005
DOI: 10.1128/iai.73.4.2452-2460.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen-DQ8 Transgenic Mice: a Model To Examine the Toxicity of Aerosolized Staphylococcal Enterotoxin B

Abstract: Staphylococcal enterotoxins (SEs) belong to a large group of bacterial exotoxins that cause severe immunopathologies, especially when delivered as an aerosol. SEs elicit the release of lethal amounts of cytokines by binding to major histocompatibility complex (MHC) class II and cross-linking susceptible T-cell receptors. Efforts to develop effective therapeutic strategies to protect against SEs delivered as an aerosol have been hampered by the lack of small animal models that consistently emulate human respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 40 publications
(75 reference statements)
3
56
0
Order By: Relevance
“…SEB is more toxic via inhalation, compared with ingestion, and severe lung damage after exposure to SEB aerosols has been demonstrated (23). Numerous animal models of SEB intoxication have been developed that use survival as a primary outcome for the efficacy of medical countermeasures (24,25). However, weaponized SEB has potential incapacitating properties for exposed military personnel because of the ED 50 (the median effective dose of incapacitation) being ∼50 times lower than the LD 50 (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…SEB is more toxic via inhalation, compared with ingestion, and severe lung damage after exposure to SEB aerosols has been demonstrated (23). Numerous animal models of SEB intoxication have been developed that use survival as a primary outcome for the efficacy of medical countermeasures (24,25). However, weaponized SEB has potential incapacitating properties for exposed military personnel because of the ED 50 (the median effective dose of incapacitation) being ∼50 times lower than the LD 50 (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Challenging HLA-II transgenic mice with SAgs thorough several different routes elicits robust SIRS and renders them highly susceptible to TSS. [40][41][42][43][44][45][46][47][48][49] One of our HLA-II transgenic lines that expresses HLA-DR3 is extremely sensitive to SEB. HLA-DR3 transgenic mice readily die of SEB-induced TSS without D-galN sensitization.…”
mentioning
confidence: 99%
“…This difference relates, in part, to the lower binding affinity of SAgs to murine MHC class II as compared with human HLA class II (21). The advent of the HLA class II transgenic (HLA-tg) mice provided an opportunity to study the pathogenesis of GAS in a readily manipulated animal model with a sensitivity to SAgs similar to that of humans (22)(23)(24)(25)(26). Indeed, several studies have shown that HLA-tg mice mount potent responses to GAS SAgs (20,23,25,27,28).…”
mentioning
confidence: 99%